PENERAPAN PRINSIP SYARIAH PEMBIAYAAN DI KOPERASI SIMPAN PINJAM SYARIAH BAITUL MAL WAT TAMWIL CAHAYA INSAN SUKOHARJO - Putra, Muh Dhzuhri Esha; Sulistyowati, S; Nissa, Izzun Khoirun (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study analyzes customer perceptions of sharia financing at the Baitul Maal Wat Tamwil Cahaya Insan Barokah Sukoharjo Savings and Loan and Financing Cooperative. The main focus is to understand how the sharia financing system is implemented and accepted by the community. The Islamic economic system, which prioritizes the principle of profit sharing and synergy between commercial and social aspects, has become a significant alternative in Indonesia's economy. Internal factors, such as the majority of the Muslim population, and external factors, such as the development of the global sharia economy, are the main drivers. This study uses a qualitative method with a case study approach to explore the effectiveness and challenges faced by sharia cooperatives in meeting customer needs while still complying with sharia principles. The results of the study show that sharia cooperatives can be an important instrument in improving the economic welfare of the community while still being based on Islamic values.